Seneca's Characters Fictional Identities and Implied Human Selves - Bexley, Erica M. (Humanities, 2022)
This book addresses the much-neglected topic of fictional character and its relationship to actual human identity. Through the lens of Senecan tragedy, it tackles questions of behavioural coherence, imitative exemplarity, physical appearance, psychology, and autonomy. It offers fresh insight into Seneca's powerful tragic aesthetics.